2020
DOI: 10.1080/17439884.2020.1798995
|View full text |Cite
|
Sign up to set email alerts
|

Historical threads, missing links, and future directions in AI in education

Abstract: Artificial intelligence has become a routine presence in everyday life. Accessing information over the Web, consuming news and entertainment, the performance of financial markets, the ways surveillance systems identify individuals, how drivers and pedestrians navigate, and how citizens receive welfare payments are among myriad examples of how AI has penetrated into human lives, social institutions, cultural practices, and political and economic processes. The effects of the algorithmic techniques employed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(82 citation statements)
references
References 38 publications
0
72
0
10
Order By: Relevance
“…Haraway criticises biology's assumption that the individual units exist before the assemblage, rather than coming into being within it. Williamson and Eynon (2020) tease out historical assemblage of threads around AI in education. In these ways, these writers gently interrupt the classificatory practices of scholars that divide assemblages into lists of elements or components or stages or processes (see also Piattoeva and Saari 2020).…”
Section: Postdigital Assemblagesmentioning
confidence: 99%
“…Haraway criticises biology's assumption that the individual units exist before the assemblage, rather than coming into being within it. Williamson and Eynon (2020) tease out historical assemblage of threads around AI in education. In these ways, these writers gently interrupt the classificatory practices of scholars that divide assemblages into lists of elements or components or stages or processes (see also Piattoeva and Saari 2020).…”
Section: Postdigital Assemblagesmentioning
confidence: 99%
“…However, increasingly critiques of AI in learning centre around the datafication of education (Jarke and Breiter, 2019;Williamson and Eynon, 2020;Selwyn, 2019a;Kwet and Prinsloo, 2020). A data driven educational system has the potential to be used or experienced as a surveillance system.…”
Section: Ai and Robotics In Research: Fiction 5 "The Research Management Suite Tm"mentioning
confidence: 99%
“…It is evident that AI developments are often partly a marketing exercise (Lacity, 2017). Edtech companies play a dominant role in developing AI (Williamson and Eynon, 2020). Selwyn (2019a) worries that those running education will be seduced by glittering promises of techno-solutionism, when the technology does not really work.…”
Section: Ai and Robotics In Research: Fiction 5 "The Research Management Suite Tm"mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the question of uptake remains understudied (see also Williamson and Eynon, 2020). Importantly, data justice and feminist scholarship have shown that some users will invariably appropriate the system in 'other' ways (e.g.…”
Section: Implications and Uptakementioning
confidence: 99%